Simulation and analysis on improving progressive collapse resistance of RC assemblies by embedding locally debonded rebars near beam-ends. (June 2022) - Yang, Xing-Ju; Lin, Feng; Gu, Xiang-Lin
Abstract: A novel method has been experimentally validated using locally debonded short rebars embedded at the beams' half-height near beam-ends to improve the progressive collapse resistance of reinforced concrete (RC) beam-column assemblies. As an extended study, this paper numerically investigated the load transfer mechanism of RC beam-column assemblies, the principle of resistance improvement by the novel method, and the influence of critical design parameters on the effectiveness of the novel method. First, the finite element models were created, with emphasis on the modeling of the bond-slip behavior of reinforcing steel bars in pre- and post-yield ranges. This behavior was found to have significant impacts on the deformation and load-carrying capacities of the RC beam-column assemblies. Second, the finite element models were validated against test data and then employed to understand the load transfer mechanisms. The resistance of the RC beam-column assemblies at the stage of small deformation was found to primarily provided by flexural/arch mechanism, reaching a maximum at middle column displacement (MCD) ≈ 0.5  h (i.e., 150 mm). Once the value of MCD exceeded h (i.e., 300 mm), the catenary mechanism was mobilized and approximately 90% of the resistance at this stage was contributed by the axially tensile force of the beams. On this basis, the principle of resistance improvement using the novel method was discussed, i.e., the progressive collapse resistance of the RC beam-column assemblies was improved through fully mobilizing catenary action and maintaining the flexural mechanism in the beams. Finally, parametric studies were conducted with consideration of the debonded length ( l pd ) and the reinforcement ratio ( ρ s, mid ) of locally debonded short rebars. Results indicated that the appropriate l pd ranged from 600 to 1000 mm, and the proper ρ s, mid varied from 1.5% to 2.2% when used in engineering practice.